Tinjauan Penerapan Prinsip Pembangunan Berkelanjutan pada Bangunan Indekos Home Sweet Home, Sukajadi, Bandung - Oktavianus Kristian Buntaran; Tessa Eka Darmayanti (Universitas Medan Area, 2023)
Boarding houses or what are often known as boarding houses are buildings that are definitely frequent and often found around campuses, especially in urban areas. A boarding house is a residential or residential building that is intended to be able to accommodate individual residents who are able to accommodate many residents. This causes the boarding house to be one of the buildings that consumes a lot of energy, is prone to generate a lot of waste, and is one of the buildings that is prone to causing environmental problems or global warming. That is why it is important for a boarding house to apply the concept of sustainable design. One of the boarding houses in the city of Bandung is Home Sweet Home which is located around the Maranatha Christian University campus. The purpose of this study was to determine the application of sustainable development principles to Home Sweet Home boarding houses. It is also hoped that this paper can help readers understand how important it is to apply the concept of sustainable design to residential buildings, especially boarding houses. The method used to collect data in writing this article is a qualitative method using a case study theory approach. The result of data analysis from writing this article is that the Home Sweet Home boarding house is a residential building that has not yet implemented a sustainable design. This also shows that there are still many boarding houses or residential buildings in big cities in Indonesia that have not yet implemented the concept of sustainable design.